SOCIO-ECONOMIC CHARACTERIZATION AND RESOURCE USE PATTERNS OF COMMUNITIES IN THE ABUAN WATERSHED - Bacquel, Jessica M.; Ramos, Agnes M. (International Journal of Psychosocial Rehabilitation, 2020)
The study aimed to determine the socio-economic characteristics and resource use patterns of the communities in Abuan watershed area. Utilizing the descriptive survey method, the research employed the quantitative and qualitative techniques supported by interviews, focus group discussions and household survey using the close-ended questionnaire administered to the 379 household residents Data were analyzed using the percentage and frequency counts to describe the socio-economic characteristics and resource use patterns of the communities in the watershed area.Findings conclude that as regards demography, majority of the total number of households surveyed are female, from Cabisera 14-16, Sindun Bayabo and Batong Labang, and with an average household size of 3-4 members in the area. Most households are Ilocano, elementary graduates, and affiliated with Roman Catholics Church. The communities’ water resources are commonly and privately owned taken from deep wells; and using electricity supply from Isabela Electric Cooperative II (ISELCO); The households benefit from health services and thy are actively involved in organizations. The income and agriculture of communities in the watershed area as regards inventory of skills reveal that majority of the respondents belong to the semi-skilled category; with livelihood activities as land owner-farmers of a farm size ranging from 2,500 to 12,499 square meters. Majority of farmer’s plant rice both in the upland rainfed and lowland type of irrigated farm; As corn and rice farmers, majority of them utilize assets and implements such as tractors, hand tractors, thresher, and water pump used in crop production, and having the livestock assets such as chickens, carabaos and pigs. The resource use patterns of the communities as source of livelihood include natural resources, forest diversity, river products, and forest products. The Abuan Watershed forest diversity natural park is underscored by the myriad of rare and endangered species of flora and fauna to support both river and forest products. The source of river products from Bintacan river included tilapia, shrimps, ikan, udang, amlid, burasi and karpa. Residents catch fish mainly for consumption. However, some respondents sell products to earn a minimum of 100 per day and amaximum of 1000 per month. Private companies also undertake quarrying activities although the community regulated this practice. Additionally, the forest products derived from Abuan watershed could be reflected in the residents’ economic activities when selling charcoal, buho, and wild pigs as source of income in barangays Batong Labang, Cabisera 8 and Sindun Bayabo.